Some crack problems in offshore pipelines - Lin, Zhiming (2016)
With the ever-rising cost of energy consumption, the demand for crude oil and natural gas has drastically increased in recent years. Offshore pipeline, one of the most economically form of transportation tool are commonly utilized for the energy resource. To construct an economically competent offshore pipeline, carbon steels with considerable plastic deformation capacity are commonly utilized. They consist of short pipeline segments connected by girth welding method and often experienced large plastic strains. This is normally due to mechanical flaws such as surface or embedded elliptical cracks observed at welding zone which posed a potential threat to the reliability of the offshore pipelines. In addition to the pipelines installed by reeling method, the large plastic bending load accompanied by high internal pressure could also pose tremendous challenges to the structural integrity of pipelines especially to the girth welds.